Influence of fibre length on the mechanical behavior of steel-PVA hybrid fibre-reinforced strain-hardening cementitious composites at high temperatures - Kumar D.; Deshpande A.A.; Ranade R. (My University, 2025)
Residual mechanical properties, after exposure to temperatures of up to 800ºC, of Hybrid Fibre-Reinforced Strain-Hardening Cementitious Composites (HFR-SHCCs) utilizing steel and polyvinyl alcohol (PVA) fibres are reported in this article. The main objective is to investigate the influence of the length of the steel fibres (13 and 25 mm) on the behavior of HFR-SHCCs. While the HFR-SHCC with 13 mm steel fibres exhibits lesser micro-cracking and greater compressive strength at room temperature than that of the HFR-SHCC with 25 mm steel fibres, the latter material shows better tensile performance at high temperatures than the former material due to higher aspect ratio of the steel fibres. © 2019, Associated Cement Companies Ltd. All rights reserved.